DAKWAH MULTIKULTURAL DI INDONESIA Studi Pemikiran dan Gerakan Dakwah Abdurrahman Wahid - Rosidi, Rosidi (Universitas Islam Negeri Raden Intan Lampung, 2013)
History records that the process of Islamization in the archipelago lasted peacefully. It was under such peaceful process that made Islam became the religion of the majority of people who had previuosly embraced Hinduism , Buddhism , and traditional religion. Some factors that influenced the success of the Islamization process are identified mainly in the form of cultural approach rather than the use of violence and military force. The recent trend, however, shows that there is a shift in the methods of religious propaganda. Many muslim missionaries tend to be intolerant, rigid, self-righteous, even with their fellow muslims. Some even use violence such as damaging a place of worship, or prevent others to worship. This study tries to identify the approaches, methods, and multicultural tendency of Abdurrahman Wahid ( Gus Dur ), who preaches Islam with friendly and peaceful manners by respecting differences and the rights of every person.